Cutaneous manifestations of COVID-19: Report of three cases and a review of literature. Issue 2 (May 2020) - Sachdeva, Muskaan; Gianotti, Raffaele; Shah, Monica; Bradanini, Lucia; Tosi, Diego; Veraldi, Stefano; Ziv, Michael; Leshem, Eyal; Dodiuk-Gad, Roni P.
Abstract: Background: Various cutaneous manifestations have been observed in patients with COVID-19 infection. However, overall similarities in the clinical presentation of these dermatological manifestations have not yet been summarized. Objective: This review aims to provide an overview of various cutaneous manifestations in patients with COVID-19 through three case reports and a literature review. Methods: A literature search was conducted using PubMed, OVID, and Google search engines for original and review articles. Studies written in the English language that mentioned cutaneous symptoms and COVID-19 were included. Results: Eighteen articles and three additional cases reported in this paper were included in this review. Of these studies, 6 are case series and 12 are case report studies. The most common cutaneous manifestation of COVID-19 was found to be maculopapular exanthem (morbilliform), presenting in 36.1% (26/72) patients. The other cutaneous manifestations included: a papulovesicular rash (34.7%, 25/72), urticaria (9.7%, 7/72), painful acral red purple papules (15.3%, 11/72) of patients, livedo reticularis lesions (2.8%, 2/72) and petechiae (1.4%, 1/72). Majority of lesions were localized on the trunk (66.7%, 50/72), however, 19.4% (14/72) of patients experienced cutaneous manifestations in the hands and feet. Skin lesion development occurred before the onset of respiratory symptoms or COVID-19 diagnosis in 12.5% (9/72) of the patients, and lesions spontaneously healed in all patients within 10 days. Majority of the studies reported no correlation between COVID-19 severity and skin lesions. Conclusion: Infection with COVID-19 may result in dermatological manifestations with various clinical presentations, which may aid in the timely diagnosis of this infection.